Climate variability and change in the spices and plantation cropping systems in Kerala state, India - Oommen, Manoj; Gopakumar, C.S.; Varghese, John Jo; Shree, A.B. Rema (Journal of Plantation Crops, 2022)
Kerala state in India has rich bio-diversity and tropical rain forests and is spread in 13 agro-ecological zones under the humid tropics. Rainfall decline (annual as well as monsoon), increase in temperature and climate shift towards lesser humid zones within the humid climate are the notable characteristics of the state. Cropping system changes, as well as changes in the production of spices and plantation crops in Kerala, were analyzed from 1952-53 to 2018-19. Area and production changes of various crops in the Idukki district have also been studied and presented in this paper. The average temperature in Kerala has risen by 0.65 °C from 1956 to 2014. In Idukki high ranges, the maximum temperature is increasing, and the minimum temperature is declining, resulting in a widening of temperature ranges. Such a scenario may adversely affect the thermo-sensitive crops, which may need urgent attention as these crops are grown in the forest-agro-ecosystems across the Cardamom Hill Reserve (CHR) of the Idukki district. Deforestation, the shift in cropping systems, declining wetlands, and depletion of surface and groundwater resources had deepened the adverse effects of floods and droughts on spice and plantation crops. Therefore, there is an urgent need for proactive steps on a short and long-term basis against the climate change risks for the sustenance of crop production both in terms of quality and volume.